Exploring multielement nanogranular coatings to forestall implant-related infections - Bottagisio, Marta; Balzano, Vincenzo; Ciambriello, Luca; Rosa, Laura; Talò, Giuseppe; Lovati, Arianna B.; De Vecchi, Elena; Gavioli, Luca (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction As we approach the post-antibiotic era, the development of innovative antimicrobial strategies that carry out their activities through non-specific mechanisms could limit the onset and spread of drug resistance. In this context, the use of nanogranular coatings of multielement nanoparticles (NPs) conjugated to the surface of implantable biomaterials might represent a strategy to reduce the systemic drawbacks by locally confining the NPs effects against either prokaryotic or eukaryotic cells. Methods In the present study, two new multielement nanogranular coatings combining Ag and Cu with either Ti or Mg were synthesized by a gas phase physical method and tested against pathogens isolated from periprosthetic joint infections to address their potential antimicrobial value and toxicity in an in vitro experimental setting. Results Overall, Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli displayed a significantly decreased adhesion when cultured on Ti-Ag-Cu and Mg-Ag-Cu coatings compared to uncoated controls, regardless of their antibiotic resistance traits. A dissimilar behavior was observed when Pseudomonas aeruginosa was cultured for 30 and 120 minutes upon the surface of Ti-Ag-Cu and Mg-Ag-Cu-coated discs. Biofilm formation was mainly reduced by the active effect of Mg-Ag-Cu compared to Ti-Ag-Cu and, again, coatings had a milder effect on P. aeruginosa, probably due to its exceptional capability of attachment and matrix production. These data were further confirmed by the evaluation of bacterial colonization on nanoparticle-coated discs through confocal microscopy. Finally, to exclude any cytotoxic effects on eukaryotic cells, the biocompatibility of NPs-coated discs was studied. Results demonstrated a viability of 95.8% and 89.4% of cells cultured in the presence of Ti-Ag-Cu and Mg-Ag-Cu discs, respectively, when compared to negative controls. Conclusion In conclusion, the present study demonstrated the promising anti-adhesive features of both Ti-Ag-Cu and Mg-Ag-Cu coatings, as well as their action in hampering the biofilm formation, highlighting the safe use of the tested multi-element families of nanoparticles as new strategies against bacterial attachment to the surface of biomedical implants.